Cognitive Structures of Space-Time - Signorelli, Camilo Miguel; Dündar-Coecke, Selma; Wang, Vincent; Coecke, Bob (Frontiers in Psychology, 2020)
In physics, the analysis of the space representing states of physical systems often takes the form of a layer-cake of increasingly rich structure. In this paper, we propose an analogous hierarchy in the cognition of spacetime. Firstly, we explore the interplay between the objective physical properties of space-time and the subjective compositional modes of relational representations within the reasoner. Secondly, we discuss the compositional structure within and between layers. The existing evidence in the available literature is reviewed to end with some testable consequences of our proposal at the brain and behavioral level.